2014
DOI: 10.1002/bjs.9401
|View full text |Cite
|
Sign up to set email alerts
|

Arm lymphoedema after axillary surgery in women with invasive breast cancer

Abstract: SLNB is associated with a minimal risk of increased arm volume and few symptoms of arm lymphoedema, significantly less than after ALND, regardless of lymph node status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…28 We have previously shown that, two years after surgery, there is a weak, yet positive, correlation between greater mean arm volume difference and self-perceived arm lymphoedema. 16 Second, the water displacement volumetry, used in the present study, offers a reliable and objective method that is considered to be the gold standard for measuring arm lymphoedema. 18,29,30 The method has, however, shortcomings especially in cases where minor arm lymphoedema is accompanied by muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 We have previously shown that, two years after surgery, there is a weak, yet positive, correlation between greater mean arm volume difference and self-perceived arm lymphoedema. 16 Second, the water displacement volumetry, used in the present study, offers a reliable and objective method that is considered to be the gold standard for measuring arm lymphoedema. 18,29,30 The method has, however, shortcomings especially in cases where minor arm lymphoedema is accompanied by muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…16 All cases were discussed both pre and post operatively at the Multidisciplinary Team Conference. At this conference, recommendations regarding adjuvant treatments with chemotherapy and/or endocrine therapy were made depending on patient's age, hormone receptor status, tumour grade and co-morbidities in accordance with the Swedish National Breast Cancer and Regional guidelines.…”
Section: Treatmentmentioning
confidence: 99%
“…The present study stems from a multicenter trial with its primary endpoint of subjective and objective assessment of arm morbidity after different types of BC surgeries at the time of introducing the sentinel node biopsy concept, a minimally invasive surgical procedure of the axilla. Four university‐affiliated breast units participated in a multicenter trial addressing arm morbidity after different types of axillary surgery . The inclusion period was 1999 to 2004, the enrollment was on a consecutive basis, and the median follow‐up time for the present study was 10 years (range 8‐12 years).…”
Section: Methodsmentioning
confidence: 99%
“…Sentinel node (SN) biopsy has proven to be a reliable method [5], and several follow-up studies have shown that it is safe to refrain from completion axillary lymph node dissection (ALND) in sentinel node-negative breast cancer [610]. The greatest advantage of the SN biopsy approach is the significant decrease in the frequency and severity of arm problems since fewer lymph nodes are removed from the axilla [1114]. …”
Section: Introductionmentioning
confidence: 99%